Shedding light on the volatile composition of broa, a traditional portuguese maize bread - Bento-Silva, Andreia (2022)
Funding Information: Funding: This research was funded by the European Union’s Seventh Framework Programme for research, technological development and demonstration under grant agreement number 245058, and by Fundação para a Ciência e Tecnologia through research unit GREEN-IT (UID/Multi/04551/2020). Funding Information: This research was funded by the European Union?s Seventh Framework Programme for research, technological development and demonstration under grant agreement number 245058, and by Funda??o para a Ci?ncia e Tecnologia through research unit GREEN-IT (UID/Multi/04551/2020). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.